Moral reasoning in knowledge authoring: An e-learning 4.0 analysis! - Costa, Gonçalo Jorge Morais da (2014)
The 21 st century has produced novel perceptions for education based on autonomous and intelligent agents that web semantics commences and e-learning 4.0 acknowledges. Therefore, it is crucial to debate what ethical and moral dilemmas arise in regard to knowledge authoring since a major shift pertaining to the concept of knowledge author can occur through moving from individuals (coordinator, tutor, or even learners) to non-human agents. However, mainstream e-learning literature seems to pay little attention to this explanandum evolution, as it merely focuses on technological development, e-learning 1.0 and 2.0 (individuals’ behavior or ethical and moral issues), moral reasoning, and education challenges. Against this background, this chapter considers challenges related to knowledge authoring in e-learning 3.0 and 4.0. For that, the chapter is divided into four sections: disclosure (guiding concepts and additional constructs); digital knowledge (from traditional to distributed knowledge, digital authorship and the importance of pedagogy); e-learning (definition, technological generations and knowledge authoring); debate (moral reasoning and ethical and moral array); future trends (an epiphany, 4.0-ethical and moral debate and an exponential epiphany)